The Quds Force and drug trafficking in the world - Ustiashvili, Samin (International Journal of Scientific Research and Management (IJSRM), 2023)
The Quds Force is one of the Islamic Revolutionary Guard Corps's five forces. It is impossible to separate the Quds force and the IRGC from each other. Since its establishment, the Islamic Revolutionary Guard Corps has supported terrorist groups in the region and Islamic countries.The "Quds Force," or the "Sepah," took its name from the title given to Jerusalem by the Islamic Republic and was formed based on Article Seven of the Islamic Revolution Guards Corps' Statute regarding the support of Islamic movements outside Iran's borders. This duty was first handled by the "Liberation Movements Unit" under the responsibility of Mohammad Montazeri and then by Mehdi Hashemi until the Unit was dissolved by the end of 1981. This Unit was also considered a sub-group of the Islamic Revolutionary Guard Corps.The "Islamic liberation movements" was also taken over by the intelligence unit of the IRGC for a while.This force was established during the Iran-Iraq war, and its purpose was to operate on Iraq's soil. Some sources have estimated this force to have up to 50,000 members worldwide.As the head of the Quds Force, Ghassem Soleimani created several other groups, such as the Hosseinioun, the Fatemiyoun, the Al-Hashd Al-Shaabi, Badr Corps, Asaib Ahl al-Haq, "Hezbollah of Iraq, in Yemen, the Quds Force supported the "Ansar Allah" group, all of these groups are politically, financially and militarily supported by the Iranian regime. Considering this organization's vast area of activities in the region, this article seeks to answer the central question of what role the Quds Force of the IRGC of Iran has played in drug trafficking in the Middle East and worldwide.1